Systemic immune-inflammation index: a key biomarker guiding personalized adjuvant chemotherapy in intrahepatic cholangiocarcinoma - Yin, Xin; Yin, Yanjiang; Li, Wenzhuo; Tong, Jinliang; Liu, Yi; Chang, Jianping; Ma, Jindong; Xie, Yaoyu; Li, Xin; Mehrabanidil, Hossein; Chen, Xiao; Zhang, Yefan; et al. (Frontiers in Oncology, 2025)
BackgroundIntrahepatic cholangiocarcinoma (ICC) is a highly aggressive primary liver malignancy, with poor long-term outcomes even after curative-intent resection. Postoperative adjuvant chemotherapy (pAC) is increasingly used, but its benefit is not uniform across all patients. The systemic immune-inflammation index (SII) has emerged as a potential prognostic marker in several cancers, but its role in ICC remains unclear.MethodsWe retrospectively analyzed 445 ICC patients who underwent R0 hepatic resection at a single tertiary center between 2000 and 2023. Preoperative SII was calculated, and patients were stratified into high- and low-SII groups. The impact of SII on overall survival (OS) and recurrence-free survival (RFS) was evaluated, along with its interaction with pAC. Multivariate Cox regression models and maximally selected rank statistics were used for analysis.ResultsThe median follow-up was 34.3 months. High SII independently predicted worse OS and RFS (p < 0.001), outperforming conventional inflammatory and nodal indices. Lymph node ratio (LNR) also independently predicted survival but did not modify the effect of pAC. Interaction analysis revealed that pAC significantly improved OS in high-SII patients (5-year OS: 33% with pAC vs. 23% without; HR 0.62, 95% CI 0.42–0.94, p = 0.022) but conferred no significant benefit in low-SII patients (5-year OS: 49% with pAC vs. 55% without; HR 0.71, 95% CI 0.48–1.05, p = 0.089).ConclusionsSII is a robust prognostic biomarker in ICC and can guide individualized postoperative therapy. High-SII patients derive substantial survival benefit from adjuvant chemotherapy, whereas low-SII patients may be spared unnecessary treatment. Integrating SII into postoperative risk stratification may optimize outcomes and reduce overtreatment in ICC.